Flux-cored wire containing surface aluminized titanium carbide particles
By using aluminum-plated titanium carbide particles in flux-core welding wire and adjusting the ratio of chromium, molybdenum and nickel, the problem of insufficiency of titanium carbide particles and the bonded metal is solved, and the wear resistance of the deposited metal is significantly improved.
Patent Information
- Application Number
- CN202510264354.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-06
AI Technical Summary
The titanium carbide particles in existing flux-core welding wires are not firmly combined with the deposited metal, which causes the titanium carbide particles to fall off easily and cannot effectively improve the wear resistance of the deposited metal.
Titanium carbide particles with surface aluminum plated are used, and the ratio of chromium powder, molybdenum powder and nickel powder is maintained at 52:96:59 in the medicament powder to promote the formation of direct chemical bonds between the titanium carbide particles and the deposited metal.
By plating aluminum and adjusting the ratio of chromium, molybdenum and nickel, the combination of titanium carbide particles and the deposited metal becomes stronger, significantly improving the wear resistance of the deposited metal, and the time taken for wear 0.5mm is increased to 1.5 times the original.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of welding materials, in particular to a flux-cored welding wire containing aluminum-plated titanium carbide particles on the surface. Background Art
[0002] Mining machinery, cement manufacturing machines, coal production equipment and other devices all require good wear resistance for key parts to ensure a long service life of the entire device. However, these easily worn parts are generally large in size and wear quickly. If they are replaced with new parts after being worn to a certain extent, the cost will be high and the production efficiency will be low. Therefore, the industry often adopts the process of surfacing a layer of wear-resistant alloy on the wear surface of easily worn parts to achieve the repair and reuse of easily worn parts, which has high production efficiency and good economic benefits.
[0003] In order to improve the wear resistance of the deposited metal during surfacing, the existing technology mostly uses flux-cored welding wire for surfacing, and the flux-cored powder contains hard phases (such as titanium carbide, etc.) to achieve the purpose of improving the wear resistance of the deposited metal. The technical problem with the current application of this process is that during the production, transportation, storage and use of the flux-cored welding wire, there will be a certain oxide film on the surface of titanium carbide particles and iron powder (the main component in the flux-cored welding wire). The titanium carbide particles will not melt during surfacing, but in the molten pool after the iron powder in the flux-cored welding wire and the parent material are melted, an oxidizing atmosphere will be formed between the titanium carbide particles and the iron atoms, and a reducing atmosphere is required for the titanium carbide particles to combine with the iron atoms. Therefore, after the deposited metal solidifies, the titanium carbide particles are not firmly bonded to the deposited metal, and the titanium carbide particles are easy to fall off during use, and the preset wear resistance purpose cannot be achieved.
[0004] Data show that after the surface of the hard phase (such as titanium carbide) is nickel-plated and then added to the flux core powder, during cladding, the nickel atoms act as a "bridge", connecting with the titanium carbide particles on one side and the iron atoms in the deposited metal on the other side, which enhances the wettability of titanium carbide. This can effectively improve the firmness of the bond between the titanium carbide particles and the deposited metal.
[0005] However, it was found in actual production that the above technology is of little help in improving the firmness of the bond between titanium carbide particles and the deposited metal, and the extent of improvement is limited. This is because relying on nickel atoms as a "bridge" to connect the titanium carbide particles and the deposited metal will inevitably form two chemical bonds (i.e., titanium-nickel and nickel-iron), making it impossible for the titanium carbide particles to be directly connected to the deposited metal, thereby weakening the connection strength between the titanium carbide particles and the deposited metal, causing the titanium carbide particles to easily fall off from the deposited metal. Summary of the invention
[0006] The invention provides a flux-cored welding wire containing aluminum-plated titanium carbide particles on the surface, which solves the following technical problem: how to directly form chemical bonds between titanium carbide particles and iron atoms in the deposited metal formed after the flux-cored welding wire is melted and solidified, so as to achieve the purpose of firmly combining the titanium carbide particles with the deposited metal matrix.
[0007] The present invention adopts the following technical solution: A flux-cored welding wire containing surface aluminum-plated titanium carbide particles, comprising an outer skin and a flux core, wherein the chemical composition and dosage of the flux core are as follows by mass percentage: surface aluminum-plated titanium carbide particles 8.0%-12.0%, aluminum powder 2.0%-3.0%, chromium powder, molybdenum powder and nickel powder 16%-20% in total, and the mass ratio of chromium powder, molybdenum powder and nickel powder is 52:96:59, ferrosilicon powder 3.0%-5.0%, ferrosilicon powder 3.0%-5.0%, ferromanganese powder 4.2%-5.8%, ferrovanadium powder 2.8%-4.0%, fluorite powder 3.2%-5.0%, rutile powder 2.8%-4.0%, calcium carbonate powder 3%-5%, and the balance is FHT100·25 reduced iron powder; The surface aluminum-plated titanium carbide particles have titanium carbide particles inside and a uniform aluminum-plated layer outside, wherein the particle size of the internal titanium carbide particles is 50 μm-70 μm, and the thickness of the external aluminum-plated layer is 5 μm-10 μm.
[0008] The filling rate of the flux core is 30%-40%, that is, the mass of the flux core accounts for 30%-40% of the total mass of the flux-cored welding wire.
[0009] The 80 mesh passing rate of the aluminum powder, ferrosilicon powder, ferromanganese powder, ferrovanadium powder, fluorite powder, rutile powder, calcium carbonate powder, and FHT100·25 reduced iron powder is 100%, which is calculated by mass percentage.
[0010] The particle sizes of the chromium powder, molybdenum powder and nickel powder are 50 meshes to 80 meshes.
[0011] Preferably, the aluminum powder is FLPA280 grade in GB / T 2085.1-2007.
[0012] Preferably, the ferrosilicon powder is the PGFeSi75Al1.5 grade in GB / T 2272-2020.
[0013] Preferably, the ferromanganese powder is of the grade FeMn82C1.5 in GB / T 3795-2014.
[0014] Preferably, the ferrovanadium powder adopts the FeV50-A grade in GB / T 4139-2012.
[0015] The outer skin is made of cold-rolled steel strip, and the thickness of the cold-rolled steel strip is 0.3mm-1.2mm.
[0016] The diameter of the flux-cored welding wire is 2.4 mm-8.0 mm.
[0017] The surface aluminum-plated titanium carbide particles are prepared by the following method: using the technical solution of Chinese patent CN101210319B, firstly, the titanium carbide particles are placed in a SnCl 2 and PdCl 2 The titanium carbide particles are immersed in a mixed solution for activation treatment, and then the titanium carbide particles are surface-chemically plated with aluminum according to the scheme of Example 2 recorded in the patent.
[0018] The uniqueness of the present invention lies in two points: (1) The surface of the titanium carbide particles added to the flux core is evenly coated with a layer of aluminum with strong reducing properties. During the welding process, the temperature of the liquid molten pool is extremely high, and the aluminum coating will quickly melt and react with the oxygen on the surface of the titanium carbide particles, consuming the oxygen so that the titanium carbide particles and the iron atoms around them are in a reducing atmosphere; the titanium atoms on the surface of the titanium carbide particles have coordinate unsaturated dangling bonds, and this special structure enables them to form a strong metal bond with the iron atoms by sharing outer electrons. If the titanium carbide surface is not plated with aluminum, or nickel, or the aluminum content in the flux core powder is simply increased, then: 1) If aluminum is not plated on the surface of titanium carbide particles, titanium-oxygen bonds are easily formed on the surface; since oxygen atoms have high electronegativity in titanium-oxygen bonds, they will seriously hinder the electron delocalization of titanium atoms and hinder the formation of titanium-iron metal bonds, making it easy for titanium carbide particles to fall off from the deposited metal matrix (see Comparative Example 1); 2) When nickel is plated on the surface of titanium carbide particles, although the formation of titanium-oxygen bonds can be avoided, due to the weak reducibility of nickel, the oxygen in the molten pool will still create an oxidizing atmosphere between the titanium carbide particles and the iron atoms, hindering the formation of titanium-iron metal bonds, making it easy for titanium carbide particles to fall off from the deposited metal matrix (see Comparative Example 2); 3) Simply increasing the aluminum content in the flux core can only enhance the reducing atmosphere in the molten pool to a certain extent, but cannot meet the strict conditions for forming titanium-iron metal bonds between titanium carbide particles and iron atoms, and will eventually cause titanium carbide particles to easily fall off from the deposited metal matrix (see Comparative Example 3); (2) The ratio of chromium powder, molybdenum powder and nickel powder in the flux core powder is 52:96:59, which ensures that the number ratio of chromium atoms, molybdenum atoms and nickel atoms is 1:1:1. Chromium, molybdenum and nickel have more d electrons. When these elements are dissolved in the iron matrix, the electron cloud of the d orbital is more complex and directional, and will interact with the electron cloud of the iron atom. Its d electrons will mix and overlap with the electron cloud of the iron atom to a certain extent, making the electron cloud distribution of the iron atom more diffuse, promoting the electrons to approach the titanium atoms on the surface of the titanium carbide particles, and increasing the tendency of the iron atoms and titanium atoms to form metal bonds. When the number ratio is 1:1:1, it is easier to form a strong metal bond; otherwise, titanium and iron are not easy to combine, which will eventually cause the titanium carbide particles to fall off from the weld metal matrix (see Comparative Example 4).
[0019] The present invention has the following beneficial technical effects: By using aluminum-plated titanium carbide particles (the first condition) and ensuring that the ratio of chromium powder, molybdenum powder and nickel powder is 52:96:59 (the second condition), the titanium atoms on the surface of the titanium carbide particles can have coordinated unsaturated dangling bonds; and the d electrons of chromium, molybdenum and nickel with more d electrons can be mixed and overlapped to a certain extent with the electron cloud of iron atoms, making the distribution of the electron cloud of iron atoms more diffuse, and promoting the electrons to approach the titanium atoms on the surface of the titanium carbide particles. Under the combined effect of the above two conditions, a strong metal bond will be formed between the iron atoms and the titanium atoms, and the titanium carbide particles are not easy to fall off from the deposited metal matrix. When the deposited metal is worn 0.5mm, the time consumed is about 1.5 times that when the above two conditions are not adopted, which effectively improves the wear resistance of the deposited metal. DETAILED DESCRIPTION
[0020] The principles and features of the present invention are described below in conjunction with embodiments and comparative examples. The enumerated embodiments and comparative examples are only used to explain the present invention and are not intended to limit the scope of the present invention.
[0021] Example 1
[0022] A flux-cored welding wire containing surface aluminum-plated titanium carbide particles, comprising an outer skin and a flux core, wherein the chemical composition and dosage of the flux core are as follows by mass percentage: 8.0% of surface aluminum-plated titanium carbide particles, 2.0% of aluminum powder, 16% of chromium powder, molybdenum powder and nickel powder in total, wherein the mass ratio of chromium powder, molybdenum powder and nickel powder is 52:96:59, 3.0% of ferrosilicon powder, 4.2% of ferromanganese powder, 2.8% of ferrovanadium powder, 3.2% of fluorite powder, 2.8% of rutile powder, 3% of calcium carbonate powder, and the balance is FHT100·25 reduced iron powder; The surface aluminum-plated titanium carbide particles have titanium carbide particles inside and a uniform aluminum-plated layer outside, wherein the particle size of the internal titanium carbide particles is 50μm-70μm, and the thickness of the external aluminum-plated layer is 5μm-10μm; The surface aluminum-plated titanium carbide particles are prepared by the following method: using the technical solution of Chinese patent CN101210319B, titanium carbide particles are firstly placed in a SnCl 2 and PdCl 2 The titanium carbide particles are immersed in a mixed solution for activation treatment, and then chemically aluminum is plated on the surface of the titanium carbide particles according to the technical scheme of Example 2.
[0023] The filling rate of the medicine core is 30%.
[0024] The aluminum powder adopts the FLPA280 brand in GB / T 2085.1-2007; the ferrosilicon powder is the PGFeSi75Al1.5 brand in GB / T 2272-2020; the ferromanganese powder is the FeMn82C1.5 brand in GB / T 3795-2014; and the ferrovanadium powder is the FeV50-A brand in GB / T4139-2012.
[0025] The 80 mesh passing rate of aluminum powder, ferrosilicon powder, ferromanganese powder, ferrovanadium powder, fluorite powder and FHT100·25 reduced iron powder is 100%.
[0026] The particle sizes of chromium powder, molybdenum powder and nickel powder are 50 mesh to 80 mesh.
[0027] The outer skin is made of cold-rolled steel strip, and the thickness of the cold-rolled steel strip is 0.3 mm.
[0028] The diameter of the flux-cored wire is 2.4 mm.
[0029] Example 2
[0030] A flux-cored welding wire containing surface aluminum-plated titanium carbide particles, comprising an outer skin and a flux core, wherein the chemical composition and dosage of the flux core are as follows by mass percentage: 12.0% of surface aluminum-plated titanium carbide particles, 3.0% of aluminum powder, 20% of chromium powder, molybdenum powder and nickel powder in total, wherein the mass ratio of chromium powder, molybdenum powder and nickel powder is 52:96:59, 5.0% of ferrosilicon powder, 5.8% of ferromanganese powder, 4.0% of ferrovanadium powder, 5.0% of fluorite powder, 4.0% of rutile powder, 5% of calcium carbonate powder, and the balance is FHT100·25 reduced iron powder; The surface aluminum-plated titanium carbide particles have titanium carbide particles inside and a uniform aluminum-plated layer outside, wherein the particle size of the internal titanium carbide particles is 50μm-70μm, and the thickness of the external aluminum-plated layer is 5μm-10μm; The surface-aluminum-plated titanium carbide particles were prepared as described in Example 1 of the present invention.
[0031] The filling rate of the core is 35%.
[0032] The aluminum powder adopts the FLPA280 brand in GB / T 2085.1-2007; the ferrosilicon powder is the PGFeSi75Al1.5 brand in GB / T 2272-2020; the ferromanganese powder is the FeMn82C1.5 brand in GB / T 3795-2014; and the ferrovanadium powder is the FeV50-A brand in GB / T4139-2012.
[0033] The 80-mesh passing rate of aluminum powder, ferrosilicon powder, ferromanganese powder, ferrovanadium powder, fluorite powder and FHT100·25 reduced iron powder is 100%.
[0034] The particle sizes of chromium powder, molybdenum powder and nickel powder are 50 mesh to 80 mesh.
[0035] The outer skin is made of H08A cold-rolled steel strip, and the thickness of the H08A cold-rolled steel strip is 0.8 mm.
[0036] The diameter of the flux-cored wire is 6.0 mm.
[0037] Example 3
[0038] A flux-cored welding wire containing surface-aluminum-plated titanium carbide particles, comprising an outer skin and a flux core, wherein the chemical composition and dosage of the flux core are as follows by mass percentage: 10.0% of surface-aluminum-plated titanium carbide particles, 2.5% of aluminum powder, 18% of chromium powder, molybdenum powder and nickel powder in total, wherein the mass ratio of chromium powder, molybdenum powder and nickel powder is 52:96:59, 4.0% of ferrosilicon powder, 5.0% of ferromanganese powder, 3.4% of ferrovanadium powder, 4.1% of fluorite powder, 3.4% of rutile powder, 4% of calcium carbonate powder, and the balance is FHT100·25 reduced iron powder; The surface aluminum-plated titanium carbide particles have titanium carbide particles inside and a uniform aluminum-plated layer outside, wherein the particle size of the internal titanium carbide particles is 50μm-70μm, and the thickness of the external aluminum-plated layer is 5μm-10μm; The surface-aluminum-plated titanium carbide particles were prepared as described in Example 1 of the present invention.
[0039] The filling rate of the core is 40%.
[0040] The aluminum powder is FLPA280 in GB / T 2085.1-2007; the ferrosilicon powder is PGFeSi75Al1.5 in GB / T 2272-2020; the ferromanganese powder is FeMn82C1.5 in GB / T 3795-2014; and the ferrovanadium powder is FeV50-A in GB / T4139-2012.
[0041] The 80-mesh passing rate of aluminum powder, ferrosilicon powder, ferromanganese powder, ferrovanadium powder, fluorite powder and FHT100·25 reduced iron powder is 100%.
[0042] The particle sizes of chromium powder, molybdenum powder and nickel powder are 50 mesh to 80 mesh.
[0043] The outer skin is made of cold-rolled steel strip, and the thickness of the cold-rolled steel strip is 1.2 mm.
[0044] The diameter of the flux-cored wire is 8.0 mm.
[0045] Comparative Example 1: It is basically the same as Example 3, except that the surface of the titanium carbide particles in the chemical composition of the core is not coated with aluminum.
[0046] Comparative Example 2: It is basically the same as Example 3, except that the surface of the titanium carbide particles in the core chemical composition is chemically nickel-plated.
[0047] Comparative Example 3: It is basically the same as Example 3, except that the surface of the titanium carbide particles in the chemical composition of the core is not coated with aluminum, but the content of aluminum powder in the core is increased to 8%.
[0048] Comparative Example 4: It is basically the same as Example 3, except that the mass ratio of chromium powder, molybdenum powder and nickel powder in the chemical composition of the core is 104:144:236, and the number ratio of chromium atoms, molybdenum atoms and nickel atoms is 2:3:4.
[0049] The flux-cored welding wires prepared in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, and 4 were used for surfacing welding of Q235 plates, with a deposited metal layer of about 3 mm. The average hardness of the deposited metal after surfacing welding was measured and a wear test was performed to measure the time taken for wear of 0.5 mm. After 5 experiments were conducted for each example of the embodiment and the comparative example, the average value of the 5 results was taken, and the results are shown in Table 1.
[0050]
[0051] It can be seen from the above embodiments and comparative examples that the surface of the titanium carbide particles in the flux-cored welding wire is not aluminum-plated, or the surface is nickel-plated, or the surface of the titanium carbide particles is not aluminum-plated but the aluminum content in the flux core powder is increased, or the ratio of chromium powder, molybdenum powder, and nickel powder is not 52:96:59, the hardness of the deposited metal is not much different, but the time taken to wear 0.5mm is greatly reduced, indicating that the titanium carbide particles are not firmly bonded to the deposited metal matrix and are easy to fall off; when the surface of the titanium carbide particles is aluminum-plated and the ratio of chromium powder, molybdenum powder, and nickel powder is 52:96:59, the titanium carbide particles are firmly bonded to the deposited metal matrix, are not easy to fall off, have good wear resistance, and the time taken to wear 0.5mm deposited metal layer is increased to about 1.5 times the original.
[0052] All equivalent changes or modifications made according to the spirit and essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A flux-cored welding wire containing surface-coated aluminum titanium carbide particles, comprising an outer sheath and a flux core, characterized in that: The chemical composition and dosage of the core are as follows by mass percentage: 8.0%-12.0% of aluminum-plated titanium carbide particles, 2.0%-3.0% of aluminum powder, 16%-20% of chromium powder, molybdenum powder and nickel powder in total, and the mass ratio of chromium powder, molybdenum powder and nickel powder is 52:96:59, 3.0%-5.0% of ferrosilicon powder, 4.2%-5.8% of ferromanganese powder, 2.8%-4.0% of ferrovanadium powder, 3.2%-5.0% of fluorite powder, 2.8%-4.0% of rutile powder, 3%-5% of calcium carbonate powder, and the balance is FHT100·25 reduced iron powder; The surface aluminum-plated titanium carbide particles have titanium carbide particles inside and a uniform aluminum-plated layer outside, wherein the particle size of the internal titanium carbide particles is 50 μm-70 μm, and the thickness of the external aluminum-plated layer is 5 μm-10 μm.
2. The flux-cored welding wire containing surface aluminum-plated titanium carbide particles according to claim 1, characterized in that: The brand of the aluminum powder is FLPA280, the brand of the ferrosilicon powder is PGFeSi75Al1.5, the brand of the ferromanganese powder is FeMn82C1.5, and the brand of the ferrovanadium powder is FeV50-A.
3. The flux-cored welding wire containing surface aluminum-plated titanium carbide particles according to claim 1, characterized in that: The 80-mesh passing rate of the aluminum powder, ferrosilicon powder, ferromanganese powder, ferrovanadium powder, fluorite powder, rutile powder, calcium carbonate powder, and FHT100·25 reduced iron powder is 100%.
4. The flux-cored welding wire containing surface aluminum-plated titanium carbide particles according to claim 1, characterized in that: The particle sizes of the chromium powder, molybdenum powder and nickel powder are 50 meshes to 80 meshes.
5. The flux-cored welding wire containing surface aluminum-plated titanium carbide particles according to claim 1, characterized in that: The filling rate of the medicine core is 30%-40%.
6. The flux-cored welding wire containing surface aluminum-plated titanium carbide particles according to claim 1, characterized in that: The outer skin is made of cold-rolled steel strip, and the thickness of the cold-rolled steel strip is 0.3mm-1.2mm.
7. The flux-cored welding wire containing surface aluminum-plated titanium carbide particles according to claim 1, characterized in that: The diameter of the flux-cored welding wire is 2.4 mm-8.0 mm.
Citation Information
Patent Citations
Chemical aluminum plating solution and chemical aluminum plating method
CN101210319B
Impact abrasion resistant flux-cored wire used for hammer head of hammer crusher
CN101602150A
Preparation method of copper-based titanium carbide / aluminum oxide surface particle strengthening composite material
CN104942268A
Titanium carbide type self-protection surfacing flux-cored wire and preparation method thereof
CN114714023A
Welding material powder, flux-cored wire and preparation method of flux-cored wire
CN119489290A